The Relationship between Mother’s Knowledge About IUDs and The Choice of Contraception in the Work Area Auxiliary Health Care Kamawen - Desy Audia Safitri; Widia Shofa Ilmiah (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2025)
Contraception is an action to prevent pregnancy, either temporarily or permanently. Intra Uterine Device (IUD) is a contraceptive method that is effective in delaying or preventing pregnancy and has the advantage of a long period of use. However, the number of IUD acceptors in the work area Auxiliary Health Care Kamawen is still low, so this research was conducted to see the relationship between maternal knowledge about IUDs and the choice of contraceptives in the work area Auxiliary Health Care Kamawen. This research used a quantitative approach with a cross sectional design, involving 40 respondents as samples, while the population was all family planning acceptors in the work area Auxiliary Health Care Kamawen of ​​Kamawen Village. Data were analyzed using the Kendall’s Tau-b correlation test. The results of the analysis show a correlation coefficient of 0.860 with a p-value of 0.000, which indicates a very strong and significant relationship between maternal knowledge and the choice of IUD contraception method. Thus, it can be concluded that the better the mother’s understanding, the higher the likelihood that they will choose IUD contraception.